Pemberdayaan Ekonomi Perempuan Melalui Pendekatan Kesetaraan Gender - Galuh Pancawati (Journal of Public Power, 2021)
The Thousand Islands Regency is the only administrative district in DKI Jakarta. Although it is located close to the center of the Indonesian government, this does not necessarily make the Thousand Islands a prosperous area. The data shows that the Thousand Islands is consistent with the highest poverty rate in DKI Jakarta, far behind other regions which were recorded at 15.06% in March 2021. Of course poverty is a development issue for decades in Indonesia, not a new thing how poverty is the face of current development. this. Taking a deeper look at how to see the mission phenomenon, this community service tries to solve the problem of poverty through glasses. Economic empowerment that is widely echoed without any gender differences does not produce a significant impact, the impact on how poverty alleviation styles that have existed so far. This community service tries to provide understanding through an initial socialization regarding the concept of gender in society. In the activity, the community was educated regarding the concept of gender where groups were combined between men and women which included 20 participants. The results of the evaluation show that there is still a low understanding of gender among social participants. Double burdens and even triple burdens are often still a problem faced by women in the Thousand Islands Regency. The unequal division of tasks becomes the starting point for knowing gender and is manifested in everyday life without realizing it. It is hoped that with this community service, the community is more literate on gender issues, starting gender justice from the smallest scope in the family scope of society.